Lung Segment Geometry Study: Simulation of Largest Possible Tumours That Fit into Bronchopulmonary Segments - Welter, S.; Stöcker, C.; Dicken, V.; Kühl, H.; Krass, S.; Stamatis, G. (The Thoracic and Cardiovascular Surgeon, 2012)
Background Segmental resection in stage I non-small cell lung cancer (NSCLC) has been well described and is considered to have similar survival rates as lobectomy but with increased rates of local tumour recurrence due to inadequate parenchymal margins. In consequence, today segmentectomy is only performed when the tumour is smaller than 2 cm.Methods Three-dimensional reconstructions from 11 thin-slice CT scans of bronchopulmonary segments were generated, and virtual spherical tumours were placed over the segments, respecting all segmental borders. As a next step, virtual parenchymal safety margins of 2 cm and 3 cm were subtracted and the size of the remaining tumour calculated.Results The maximum tumour diameters with a 30-mm parenchymal safety margin ranged from 26.1 mm in right-sided segments 7 + 8 to 59.8 mm in the left apical segments 1–3.Conclusions Using a three-dimensional reconstruction of lung CT scans, we demonstrated that segmentectomy or resection of segmental groups should be feasible with adequate margins, even for larger tumours in selected cases.
Keywords: segmentectomy; lung cancer; safety margins; resection planning; three-dimensional reconstruction; volume of segments